Almost Everyone Loses Meaning in Life From Social Exclusion, but Some More Than the Others: A Comparison Among Victims, Voluntary, and Forced Rejecters - Zhang, Shuyue; Huang, Junqing; Duan, Hedan; Turel, Ofir; He, Qinghua (Frontiers in Psychology, 2021)
Social exclusion has been a major societal concern because it hinders the attainment of needs for belonging and relationship. While we know much about the effects of social exclusion on victims and perpetrators, there is limited insight regarding how different types of rejecters (voluntary vs. forced) might affect important outcomes. The purpose of this study is to bridge this gap and to examine how different types of social exclusion (forced and voluntary) influence meaning in the life of participants. To this end, we conducted two experiments using two social exclusion paradigms: the recall paradigm and the Cyberball game. The results of the two experiments were consistent. Both experiments revealed that (1) the meaning in the life of the victim group and the forced rejecter group (i.e., those who were forced to exclude others) was significantly lower than this of the control group and the voluntary rejecter group (i.e., those choosing to exclude others). There were no significant differences between the victim group and the forced rejecter group, and there were no significant differences between the voluntary rejecter group and the control group. These results reveal that social exclusion not only negatively affects the victims of exclusion but also reduces the meaning in the life of forced rejecters. These findings are specific, and they show that the types of will in exclusion can create differences in the effects of social exclusion on the rejecters.